Construction of mother's knowledge regarding bottle feeding in neonatal regurgitation incidents - Yulianti N; Darwin, Devi; Irmayanti, Irmayanti (Jurnal Konseling dan Pendidikan, 2025)
Regurgitation or Spitting Up is a normal thing that happens to babies, especially after breastfeeding. Regurgitation in small amounts, which is sometimes accompanied by burping, is usually nothing to worry about. However, if spitting up happens very often and in large amounts, it could be caused by giving too much milk. To overcome this, use a harder nipple and a smaller hole if the baby drinks milk from a bottle. In addition, get used to burping the baby more often during and after breastfeeding, both for babies who drink breast milk and formula milk. study aims to analyze the relationship between Pregnant Women's Knowledge Regarding Bottle Feeding on Neonatal Regurgitation Incidents at Seko Barat Health Center, North Luwu Regency. The research design used Cross Sectional Study. The subjects of the study were mothers who had babies aged 0-3 months with a total of 30 samples. The data collection technique used a questionnaire then the data was analyzed using the chi square test. The results of the study were obtained from the analysis test using the Chi Square Test method indicating a significant relationship between Pregnant Women's Knowledge Regarding Bottle Feeding and the Incident of Neonatal Regurgitation at the Seko Barat Health Center, North Luwu Regency in 2024. workers can improve the quality of health services by regularly providing information and counseling to mothers of toddlers about bottle feeding and how to burp babies. This effort is expected to increase knowledge and improve maternal behavior so that babies do not experience regurgitation.